Modelling the significance of value-belief-norm theory in predicting workplace energy conservation behaviour - Al Mamun, Abdullah; Hayat, Naeem; Mohiuddin, Muhammad; Salameh, Anas A.; Ali, Mohd Helmi; Zainol, Noor Raihani (Frontiers in Energy Research, 2022)
A country’s energy usage can depict the development of its economy. Excessive energy consumption generates carbon emissions that degrade the climate and present challenges for sustainable global development. China is achieving economic development with excessive energy consumption and excessive carbon emissions, damaging the climate. As more energy is consumed at workplaces than in households and other buildings, energy conservation behaviors at workplaces can help mitigate environmental issues. In this study, we explore energy conservation behaviors in the workplace using the value-belief-norm (VBN) theory that has been extended and tested with survey data collected from China. Online survey-based data were collected from a total of 1,061 respondents and analyzed with partial least square regression structural equation modelling (PLS-SEM). The results of our analysis indicate that biospheric values significantly predict pro-environment beliefs, awareness of consequences, and ascription of responsibility. Moreover, pro-environment beliefs positively affect awareness of consequences, and awareness of consequences positively affects the ascription of responsibility. Findings further revealed that pro-environment beliefs, awareness of consequences, an ascription of responsibility, and social norms positively affect personal norms. Furthermore, social and personal norms lead to intentions to engage in energy conservation behavior, which influences energy conservation behavior in the workplace. The current study contributes to our knowledge and understanding about workplace energy conservation behaviors by constructing biospheric values that lead to developing the necessary beliefs and norms to activate energy conservation behaviors. Policy and managerial implications are reported, which involve inculcating the necessary values and beliefs that generate norms that lead to pro-climate behavior.